Anishinaabe Law at the Margins: Treaty Law in Northern Ontario, Canada, as Colonial Expansion - Brown, Tenille E. (Social Inclusion, 2023)
In 1850, 17 years before the Dominion of Canada was created, colonial officers in representation of Her Majesty the Queen, concluded Treaty Numbers 60 and 61 with the Anishinaabe Nation of Northern Ontario. The Robinson Treaties - so named after William Benjamin Robinson, a government official - include land cessions made by the Anishinaabe communities in return for ongoing financial support and protection of hunting rights. The land areas included in the treaty are vast territories that surround two of Canada's great lakes: Lake Superior and Lake Huron. These lands were important for colonial expansion as settlements began to move west across North America. The treaties promised increased annual annuity payments "if and when" the treaty territory produced profits that enabled "the Government of this Province, without incurring loss, to increase the annuity hereby secured to them." This amount has not been increased in 150 years. This article reviews Restoule v. Canada, a recent Ontario decision brought by Anishinaabe Treaty beneficiaries who seek to affirm these treaty rights. A reading of the Robinson Treaties that implements the original treaty promise and increases annuity payments would be a hopeful outcome of the Restoule v. Canada decision for it would be the implementation of reconciliation. In addition, the Restoule decision has important insights to offer about how Indigenous law can guide modern‐day treaty interpretation just as it guided the adoption of the treaty in 1850. The Robinson Treaties are important for the implementation of treaty promises through Indigenous law and an opportunity to develop a Canada in which Indigenous peoples are true partners in the development and management of natural resources.